Apple and Annie, the Hamster Duo - Florence, Debbi Michiko; Demmer, Melanie (Oxford : Raintree, 2020)
Annie and Apple are a pair of chatty, restless dwarf hamsters from the animal shelter who are being fostered by eight-year-old Kaita Takano and her family. Kaita can't wait to find forever homes for the inquisitive furballs -- but first, she has to find them! Bright, engaging illustrations and 1st-person narration invite early chapter-book readers into the nonstop fun and adventure.
Ages 4-7.
Keywords: Hamsters as pets -- Juvenile fiction; Foster care of animals -- Juvenile fiction; Children's stories